2007
DOI: 10.1002/rsa.20161
|View full text |Cite
|
Sign up to set email alerts
|

Level of nodes in increasing trees revisited

Abstract: ABSTRACT:Simply generated families of trees are described by the equation T (z) = ϕ(T (z)) for their generating function. If a tree has n nodes, we say that it is increasing if each node has a label ∈ {1, . . . , n}, no label occurs twice, and whenever we proceed from the root to a leaf, the labels are increasing. This leads to the concept of simple families of increasing trees. Three such families are especially important: recursive trees, heap ordered trees, and binary increasing trees. They belong to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 12 publications
1
72
0
Order By: Relevance
“…Considering the above insertion rule, the parent u of the nth internal node is chosen with probability proportional to b − deg(u), where deg(u) is the number of internal children of node u in the tree with n − 1 nodes and each of the deg(u) + 1 possible positions for the new node are equally likely. In Panholzer and Prodinger (2007) and Kuba and Panholzer (2010) it was shown that this tree is the same as the b-ary increasing tree, which belongs to the simple families of increasing trees introduced in Bergeron et al (1992). In Drmota (2009, Section 1.3.3) this tree is also called the b-ary recursive tree.…”
Section: Random Weighted B-ary Recursive Treesmentioning
confidence: 99%
“…Considering the above insertion rule, the parent u of the nth internal node is chosen with probability proportional to b − deg(u), where deg(u) is the number of internal children of node u in the tree with n − 1 nodes and each of the deg(u) + 1 possible positions for the new node are equally likely. In Panholzer and Prodinger (2007) and Kuba and Panholzer (2010) it was shown that this tree is the same as the b-ary increasing tree, which belongs to the simple families of increasing trees introduced in Bergeron et al (1992). In Drmota (2009, Section 1.3.3) this tree is also called the b-ary recursive tree.…”
Section: Random Weighted B-ary Recursive Treesmentioning
confidence: 99%
“…It is interesting to ask which other simple classes of increasing trees admit such a construction (via a natural tree evolution process). This question was solved in Panholzer and Prodinger [24], where it was shown that up to scaling such a construction exists if and only if the class belongs to following three types.…”
Section: Other Simple Classes Of Increasing Treesmentioning
confidence: 99%
“…In a recent paper Panholzer and Prodinger [12] proved that there are exactly three families where the sequence P n of probability measures on J n is induced by a (natural) tree evolution process (described below) if and only if Ψ(t) has one of the three forms:…”
Section: The Probabilistic Modelmentioning
confidence: 99%
“…Note that for every scaling factor c > 0 the function F (c y) is also a solution of (12). Thus, we can assume (without loss of generality) that there is F α that satisfies (12) and…”
Section: D-ary Increasing Treesmentioning
confidence: 99%
See 1 more Smart Citation